Tension Force-Induced ATP Promotes Osteogenesis Through P2X7 Receptor in Osteoblasts - Kariya, Taro (J Cell Biochem, 2015)
Orthodontic tooth movement induces alveolar bone resorption and formation by mechanical stimuli. Force exerted on the traction side promotes bone formation. Adenosine triphosphate (ATP) is one of the key mediators that respond to bone cells by mechanical stimuli. However, the effect of tension force (TF)-induced ATP on osteogenesis is inadequately understood. Accordingly, we investigated the effect of TF on ATP production and osteogenesis in MC3T3-E1 cells. Cells were incubated in the presence or absence of P2X7 receptor antagonist A438079, and then stimulated with or without cyclic TF (6% or 18%) for a maximum of 24 h using Flexercell Strain Unit 3000. TF significantly increased extracellular ATP release compared to control. Six percent TF had maximum effect on ATP release compared to 18% TF and control. Six percent TF induced the expression of Runx2 and Osterix. Six percent TF also increased the expression of extracellular matrix proteins (ECMPs), ALP activity, and the calcium content in ECM. A438079 blocked the stimulatory effect of 6% TF on the expression of Runx2, Osterix and ECMPs, ALP activity, and calcium content in ECM. This study indicated that TF-induced extracellular ATP is released in osteoblasts, suggesting that TF-induced ATP promotes osteogenesis by autocrine action through P2X7 receptor in osteoblasts. J. Cell. Biochem. 116: 12–21, 2015. © 2014 The Authors. Journal of Cellular Biochemistry published by Wiley Periodicals, Inc.